Identification of the Antithrombotic Mechanism of Leonurine in Adrenalin Hydrochloride-Induced Thrombosis in Zebrafish via Regulating Oxidative Stress and Coagulation Cascade - Liao, Li; Zhou, Mengting; Wang, Jing; Xue, Xinyan; Deng, Ying; Zhao, Xingtao; Peng, Cheng; Li, Yunxia (Frontiers in Pharmacology, 2021)
Thrombosis is a general pathological phenomenon during severe disturbances to homeostasis, which plays an essential role in cardiovascular and cerebrovascular diseases. Leonurine (LEO), isolated from Leonurus japonicus Houtt, showed a crucial role in anticoagulation and vasodilatation. However, the properties and therapeutic mechanisms of this effect have not yet been systematically elucidated. In this study, the antithrombotic effect of LEO was investigated in AH-induced thrombosis in zebrafish larvae. Reactive oxygen species (ROS) generation in zebrafish was investigated by using fluorescence probes. LDH, MDA, SOD, GSH, as well as ET-1, and nitric oxide (NO) were analyzed by kits. Besides, we detected the expression of related genes and proteins related to the anticoagulation and fibrinolytic system by quantitative polymerase chain reaction (PCR) and western blot. Beyond that, metabolomic analyses using liquid chromatography-mass spectrometry were carried out to identify the expressions of metabolites associated with the anti-thrombosis mechanism of LEO. Our results suggested that the antithrombotic effect of LEO may relate to the resistance of oxidative stress injury, inhibition of coagulation cascade and platelet activation, and modulation of amino acid and inositol metabolites.